2019
DOI: 10.5505/pajes.2019.89990
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects on Rheological and Filtration Properties of Water-Based Drilling Mud of Boron Minerals: An Experimental Study

Abstract: ÖzThe aim of this study is to determine the effect on the rheological and filtration properties of water based drilling fluid of boron minerals. For this purpose, water-based drilling mud was prepared and borax (Na2B4O7.10H2O) with a particle size of 45 μm, ulexite (NaCaB5O9.8H2O) with a particle size of 75 μm and colemanite (Ca2B6O11.5H2O) with a particle size of 100 μm with different concentrations 1-5 (% w/v) are separately added. The characterization of borax, uleksite and colemanite are examined using X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
5
0
4
Order By: Relevance
“…Boron needs to be removed from flowback before its possible reuse as "frac water" [51]. On the other hand Ozkan and Kaplan [52] observed that boron additives improve the rheological properties of the drilling mud and only slightly hinder its filtration properties.…”
Section: Inorganic Constituents In Flowback Watermentioning
confidence: 99%
“…Boron needs to be removed from flowback before its possible reuse as "frac water" [51]. On the other hand Ozkan and Kaplan [52] observed that boron additives improve the rheological properties of the drilling mud and only slightly hinder its filtration properties.…”
Section: Inorganic Constituents In Flowback Watermentioning
confidence: 99%
“…Çamur yoğunlukları, ilgili API standardı uyarınca Fann 140 Çamur Terazisi kullanılarak belirlenmiştir. Görünür viskozite (μa), plastik viskozite (μp) ve akma noktası (τy) gibi reolojik özellikler, Fann 280 Döner Viskozimetre ile 300 ve 600 devir/dakika değerlerinde gerçekleştirilen viskozite ölçümlerinden (θ300 ve θ600) aşağıdaki eşitlikler yardımıyla hesaplanmıştır (Özkan & Kaplan, 2019).…”
Section: çAmur Testleriunclassified
“…Katkısız çamurlar için elde edilen genel sonuçlar, kullanılan numunenin ilgili API standardına göre %6 katı içeriği için OCMA kalite bir bentonitte aranan tüm spesifikasyonları sağladığını göstermiştir. Bununla birlikte, plastik viskozite alt limiti için bazı kaynaklarda verilen 7 ve 10 cp değerleri, %6 bentonit içeriği için karşılanamamaktadır (Çinku, 2008;Özkan & Kaplan, 2019). Diğer bir deyişle, numunenin pratikte polimer katkısız olarak kullanımının zor olduğu söylenebilir.…”
Section: Katkısız çAmur Testleriunclassified
See 1 more Smart Citation
“…Sondaj operasyonlarını sıkıntısız bir şekilde tamamlamak ve maliyetini düşürmek için, sondaj çamurlarının reolojik ve filtrasyon özelliklerinin geliştirilmesine yönelik çalışmalar her geçen gün artarak devam etmektedir. Özellikle nano ve mikro boyutlu malzemeler eklenerek sondaj çamurlarının özelliklerinin daha da iyileştirilmesi hedeflenmektedir [6][7][8][9][10]. Nano boyutlu malzemeler 1-100 nm boyutunda olup oldukça geniş yüzey alanına sahip olmasından dolayı kuyu stabilitesini arttırarak delme işlemini kolaylaştırmak, açığa çıkan kırıntıların rahat bir şekilde yüzeye taşınması sağlamak, filtrasyon kaybını ve kek kalınlığını azaltmak gibi birçok sondaj sorununun çözülmesinde önemli katkıda bulunmaktadırlar [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionunclassified